Morphological and molecular evidence for a new species of longnose skate (Rajiformes: Rajidae: Dipturus) from Argentinean waters based on DNA barcoding - de Astarloa, Juan Martin Díaz; Mabragaña, Ezequiel; Hanner, Robert; Figueroa, Daniel E. (Zootaxa, 2008)
A new species of Dipturus is described from ten specimens collected off Patagonia, Argentina. Morphological and molecular approaches were used to compare among specimens of recognized Dipturus species. By comparing morphometric, meristic and mitochondrial cytochrome c oxidase I (COI) sequence data, specimens referred to as longnose skate and originally regarded as D. chilensis were shown to be a discrete species as distinguished from both the Yellownose skate, D. chilensis and the Roughskin skate, D. trachyderma. Dipturus argentinensis n. sp. can be distinguished from all other southwestern Atlantic longnose skate species by its color pattern, lack of squamation on both upper and lower surfaces of the disc, and a long, thin tail that is approximately half the total length. The new species has one median row of 10 to 24 small caudal thorns, one or two interdorsal thorns and 35 to 40, and 34 to 43 tooth rows on upper and lower jaws, respectively. The 648 base pair COI mitochondrial DNA “barcodes” derived from specimens of D. argentinensis are identical to each other and exhibit greater than 3% sequence divergence from all other Dipturus species similarly characterized to date. Taken together, these independent morphological and molecular observations serve to corroborate one another and thus provide strong evidence for the recognition of D. argentinensis as a new species.